2006
DOI: 10.2519/jospt.2006.36.3.152
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Cervical Radiculopathy Using a Clinical Prediction Rule and a Multimodal Intervention Approach: A Case Series

Abstract: Study Design: Case series. Objectives: To describe an established method of diagnosing cervical radiculopathy (CR) using a clinical prediction rule (CPR), and to describe the management of 6 patients using intermittent cervical traction (ICT), thoracic thrust joint manipulation (TJM), and exercise. Background: Many patients present with unilateral arm pain without having undergone magnetic resonance imaging (MRI) of the cervical spine. Using a CPR has demonstrated high levels of specificity to rule in cervical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 44 publications
0
28
0
2
Order By: Relevance
“…While preliminary reports suggest that a multimodal treatment program consisting of manual therapy and exercise may result in positive outcomes for patients with CR, [6][7][8][9][10] efforts to successfully add cervical traction to a multimodal treatment program remain elusive. A study by Ragonese 11 concluded that when treating patients with a diagnosis of CR, an approach that combines manual therapy (including cervical traction) and therapeutic exercise appears to be superior to either intervention alone.…”
Section: Introductionmentioning
confidence: 99%
“…While preliminary reports suggest that a multimodal treatment program consisting of manual therapy and exercise may result in positive outcomes for patients with CR, [6][7][8][9][10] efforts to successfully add cervical traction to a multimodal treatment program remain elusive. A study by Ragonese 11 concluded that when treating patients with a diagnosis of CR, an approach that combines manual therapy (including cervical traction) and therapeutic exercise appears to be superior to either intervention alone.…”
Section: Introductionmentioning
confidence: 99%
“…As the head is lifted against gravity, the CCF muscles are trained in their capacity to prevent gravity-induced craniocervical extension, as indicated by a forward thrust of the chin. 2,9,37 Although both craniocervical flexion and cervical flexion movements utilize the CCF muscle group, 27 there are fundamental differences between these exercises. Specifically, craniocervical flexion occurs principally about the upper cervical motion segments, 10,34,38 while cervical flexion, although involving multiple cervical motion segments, can be primarily resolved to motion about the cervicothoracic junction.…”
mentioning
confidence: 99%
“…Figure 1 illustrates the results of search strategy for potential articles. Following the initial exclusion of articles from database searches and after a review of potentially relevant articles obtained from database searches, manual searches, and authors, 21 obtained articles were excluded for the following reasons: case study/series 3,6,9,15,20,23,35 , use of mobilization instead of manipulation [36][37][38][39] , purpose being biomechanical/ physiological documentation 30,40,41 , cohort designs 11,12 , primarily informational 42,43 , one group pretest/post-test design 5 , follow-up of a previous RCT 44 , or subjects were younger than 18 years of age 45 . Eight authors were identified and emailed to find out if they were aware of other articles on TSM.…”
Section: Article Selectionmentioning
confidence: 99%